Sequential Combustion in Steam Methane Reformers for Hydrogen and Power Production With CCUS in Decarbonized Industrial Clusters - Herraiz, Laura; Lucquiaud, Mathieu; Chalmers, Hannah; Gibbins, Jon (Frontiers in Energy Research, 2020)
In future energy supply systems, hydrogen and electricity may be generated in decarbonised industrial clusters using a common infrastructure for natural gas supply, electricity grid and transport and geological storage of CO2. The novel contribution of this article consists of using sequential combustion in a steam methane reforming (SMR) hydrogen plant to allow for capital and operating cost reduction by using a single post-combustion carbon capture system for both the hydrogen process and the combined cycle gas turbine (CCGT) power plant, plus appropriate integration for this new equipment combination. The concept would be widely applied to any post-combustion CO2 capture process. A newly developed, rigorous, gPROMs model of two hydrogen production technologies, covering a wide range of hydrogen production capacities, thermodynamically integrated with commercially available gas turbine engines quantifies the step change in thermal efficiency and hydrogen production efficiency. It includes a generic post-combustion capture technology – a conventional 30%wt MEA process - to quantify the reduction in size of CO2 absorber columns, the most capital intensive part of solvent-based capture systems. For a conventional SMR located downstream of an H-class gas turbine engine, followed by a three-pressure level HRSG and a capture plant with two absorbers, the integrated system produces ca. 696,400 Nm3/h of H2 with a net power output of 651 MWe at a net thermal efficiency of 38.9 %LHV. This corresponds to 34 MWe of additional power, increasing efficiency by 4.9 % points, and makes one absorber redundant compared to the equivalent non-integrated system producing the same volume of H2. For a dedicated gas heated reformer (GHR) located downstream of an aeroderivative gas turbine engine, followed by a two-pressure level HRSG and a capture plant with one absorber, the integrated system produces ca. 80,750 Nm3/h of H2 with a net power output of 73 MWe and a net thermal efficiency of 54.7 %LHV. This corresponds to 13 MWe of additional power output, increasing efficiency by 13.5 % points and also makes one absorber redundant. The article also presents new insights for the design and operation of reformers integrated with gas turbines and with CO2 capture.